Update breast cancer 2021 part 5 - Advanced breast cancer = Update Mammakarzinom 2021 Teil 5 - fortgeschrittenes Mammakarzinom - Lüftner, Diana; Schütz, Florian; Stickeler, Elmar; Fasching, Peter A.; Janni, Wolfgang; Kolberg-Liedtke, Cornelia; Kolberg, Hans-Christian; Thomssen, Christoph; Müller, Volkmar; Fehm, Tanja; Belleville, Erik; Bader, Simon; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Despite the COVID 19 pandemic and mostly virtual congresses, innovation in the treatment of breast cancer patients continues at an unabated pace. This review summarises the current developments. Initial overall survival data for CDK4/6 inhibitor treatment in combination with an aromatase inhibitor as the first advanced line of therapy in treatment-naive postmenopausal patients have been published. Similarly, a trial comparing trastuzumab-deruxtecan versus trastuzumab-emtansine revealed a clear benefit regarding progression-free survival. Understanding of biomarkers making checkpoint inhibitor therapy particularly effective is increasing, and new compounds such as oral selective estrogen receptor destabilisers (SERDs) are entering clinical development and completing the first phase III trials.
Gesehen am 16.11.2022